Inquiry Examination and Forensic Analysis of Objects in the Investigation of Iatrogenic Crimes - M. V. Tuzlukova (Теория и практика судебной экспертизы)
The article presents some forensic technical and tactical features of the inquiry examination and forensic analysis of objects in the investigation of iatrogenic crimes. The objects of the inquiry examination are, first of all, medical devices and tools, drugs and patient care products, computer equipment.The author reviews the practice of detecting and investigating cases of the abandonment of foreign objects in a patient’s body by medical personnel. She also analyses the specifics of the appointment, production, and assessment of forensic traceological and computer examinations, during which the study of discovered and seized items is carried out.